PARADIGMA MODERASI MUHAMMAD MUTAWALLI AL-SYA’RAWI - Hilman Hujaji (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2024)
The focus of this research is to find out more about Muhammad Mutawalli Al-Sya'rawi's moderation paradigm in his commentary book, Tafsîr Al-Sya'râwî. By presenting Al-Sya'rawi's views, understanding, and interpretation of the verses that form the basis of religious moderation directly from his monumental work, Tafsîr Al-Sya'râwî, this research uses library research methods. The author collects data and processes the data using descriptive analytical and comparative methods to compare the various opinions found.